Calagem superficial em área de plantio direto - Chapla, Marlus Eduardo (2017)
The base saturation method for liming determination has apparently underestimated the ideal amount of limestone required by the crops. The objective of this work was to evaluate the effects of surface limestone application on soil chemical characteristics and corn and soybean crop development and production. For this, an experiment was carried out in the municipality of SinopMT, in an area under commercial tillage under a no-tillage system for more than 15 years, under soybean-corn cultivation annually. The treatments were schematized in a 2x4 factorial, with 2 types of calcareous (calcitic and dolomitic) and 4 doses (0,0, 1,7, 3,4 and 5,1 t.ha-1), with 3 replicates. The experiment was conducted from August 2014 to June 2016. Chemical soil attributes were evaluated in the layers 0-5, 5-10 and 10-20 at 10 months and 0-20 cm at 22 months after application of limestone , besides the development and productivity of corn and soybean crops in 2 harvests (2015 and 2016). The increase in pH and the reduction of potential acidity occurred in response to the application of limestone doses. The liming promoted increases in the Ca, Mg and base saturation levels in superficial layers at the 10 months most concentrated in the superficial layers, and at 22 months after application, promoted increments in the 0-20 cm layer. The development and yield of soybean and maize in the first harvest (2015) were not influenced by surface liming. In the second crop, there were significant increases in both corn and soybean yield and yield in response to the rates and types of limestone, with the greatest effect observed with the application of calcitic limestone.